college

posted by .

Evaluate the difference quotient for the given function. Simplify your answer.
f(x) = 3 + 5x − x2,
f(4 + h) − f(4)
h

  • math -

    Did you notice that you were asked to type your School Subject?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    First, give the technology formula for the given function and then use technology to evaluate the function for the given values of x. (Round your answers to four decimal places.) r(x) = 4x2 + 1/4x2 − 1; x = −1, 0, 1, ..., …
  2. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  3. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  4. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  5. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  6. Math

    Simplify the difference quotient [f(2 + h) − f(2)]/h if h ≠ 0. f(x) = x^2 − 3x I keep getting the answer wrong...please help.
  7. Mathematics

    Simplify the difference quotient [f(x) − f(a]/[x − a] if x ≠ a. f(x) = SQROOT of (x − 27) (Hint: Rationalize the numerator.)
  8. Pre-Calc

    Simplify the difference quotient [f(2 + h) − f(2)]/h ; if h ≠ 0. f(x) = x2 − 3x I keep getting the answer wrong. I must be messing up my steps...Please Help
  9. Calculus 1

    Evaluate the difference quotient for the given function. Simplify your answer. f(x) = 1+2x− x^2, (f(4+h)-f(4))/h
  10. Calculus

    Find the first partial derivatives and evaluate each at the given point. Function w = 2x^2y − 6xyz + 10yz^2 Point (2, 5, −3) wx(2, 5, −3) = wy(2, 5, −3) = wz(2, 5, −3) =

More Similar Questions